Extracellular polymeric substance produced by Lysinibacillus sp. SS1 in response to petroleum crude oil stress facilitates removal of heavy metals from aqueous solutions - Miyar, Harshitha Kamath; Pai, Annapoorna; Sajankila, Shyama Prasad; Goveas, Louella Concepta (2020)
TThe use of microbial extracellular polymeric substances (EPS) as bioflocculants opposed to synthetic and organic flocculants in the treatment of heavy metal polluted wastewater is currently gaining importance. The present study focuses on the characterization and application of EPS produced by Lysinibacillus sp. SS1 in heavy metal removal. Lysinibacillus sp. SS1 (10%v/v), isolated from used engine oil contaminated soil, produced EPS and circular white spongy masses on the utilization of 3% petroleum crude oil (PCO) in the Bushnell Haas medium in 10 d. Analysis of extracted EPS and masses revealed that it contained carbohydrates, lipids, and proteins in proportions of 1.3: 94.6: 3.6 and 2.3: 91.5: 6.2, respectively. Characterization by LCMS and FT-IR analysis confirmed that they were predominantly lipids with proteins and polysaccharide groups. Masses could remove 48% of lead and 40% of mercury from aqueous solutions by adsorption on their surface as confirmed by SEM-EDAX. Extracted EPS (100 mg/L) could remove 94.9% of lead from aqueous solution (150 mg/L) in 72 h by precipitation of lead as nanoparticles of sizes ranging from 30?40 nm. This study shows the potential of Lysinibacillus sp. SS1 and its EPS in response to PCO in heavy metal removal and recovery.